Fish Scale Gelatin Nanofibers with Helichrysum italicum and Lavandula latifolia Essential Oils for Bioactive Wound-Healing Dressings - Carmen Gaidau; Maria Râpă; Maria Stanca; Mariana-Luiza Tanase; Laura Olariu; Rodica Roxana Constantinescu; Andrada Lazea-Stoyanova; Cosmin-Andrei Alexe; Madalina Tudorache (MDPI AG, 2023)
Essential oils are valuable alternatives to synthetic antibiotics that have the potential to avoid the pathogen resistance side effects generated by leather. Helichrysum italicum and Lavandula latifolia essential oils combined with fish scale gelatin were electrospun using a coaxial technique to design new bioactive materials for skin wound dressings fabrication. Fish scale gelatins were extracted from carp fish scales using two variants of the same method, with and without ethylenediaminetetraacetic acid (EDTA). Both variants showed very good electrospinning properties when dissolved in acetic acid solvent. Fish scale gelatin nanofibers with Helichrysum italicum and Lavandula latifolia essential oil emulsions ensured low microbial load (under 100 CFU/g of total number of aerobic microorganisms and total number of yeasts and filamentous fungi) and the absence of Staphylococcus aureus ATCC 6538, Escherichia coli ATCC 10536, and Candida albicans ATCC 1023 as compared to fish scale gelatin without essential oils, which recommends them for pharmaceutical or topical applications. A scratch-test performed on human dermal fibroblasts proved that the biomaterials contributing to the wound healing process included fish scale gelatin nanofibers without EDTA (0.5% and 1%), fish scale gelatin nanofibers without EDTA and Lavandula latifolia essential oil emulsion (1%), fish scale gelatin nanofibers with EDTA (0.6%), and fish scale gelatin nanofibers with EDTA with Helichrysum italicum essential oil emulsion (1% and 2%).